Perbedaan Kadar Albumin Plasma Pada Pasien Sebelum dan Setelah Menjalani Rawat Inap di RSUD PROF. DR Margono Soekarjo Purwokerto - Saryono,; Prastowo, Agus; Anggraeni, Mekar Dwi (Jurusan Keperawatan FIKES UNSOED, 2006)
The malnutrition rate in Indonesian hospital was hightly about 75%. The determinant of nutrition states with biochemically known by the concentration of plasma albumin. Albumin is the protein of the highest concentration in plasma. Albumin transports many small molecules in the blood (for example: bilirubin, calcium, progesterone, and drugs). It is also of prime importance in maintaining the oncotic pressure of the blood (that is, keeping the fluid from leaking out into the tissues). Decreased albumin may also be caused by malnutrition or a low protein diet. The aims of this research was to determine change in albumin before and after hospitalization in Margono Soekarjo Hospital, Purwokerto. It was analytic research with cross sectional study. The study population consisted of 69 subjects. The albumin concentrations was determined at before and after hospitalization. The average of albumin concentrations before and after hospitalization were 2,88 g/L and 2,52 g/L respectively. The t test showed that albumin concentrations after hospitalization decrease significantly (p